Effects of active learning classrooms on student learning: a two-year empirical investigation on student perceptions and academic performance. Issue 2 (23rd February 2017) - Chiu, Pit Ho Patrio; Cheng, Shuk Han
ABSTRACT: Recent studies on active learning classrooms (ACLs) have demonstrated their positive influence on student learning. However, most of the research evidence is derived from a few subject-specific courses or limited student enrolment. Empirical studies on this topic involving large student populations are rare. The present work involved a large-scale two-year study that examined the effects of ACL on student perceptions of their learning experience and the relationship with academic performance in a General Education programme. An institutional survey was used to gather more than 35, 000 units of student perception data from all 306 courses in the programme. Our empirical findings show that students thought courses that adopted an ACL as the key learning environment were significantly better designed and more encouraging of student creativity and innovation than courses which used regular classrooms; thus, student perceptions were improved. We are also the first to report that this positive effect on creativity and innovation is statistically unaffected by academic performance, with high, middle and low achievers all benefiting from the use of the facility. The results suggest that ACLs are better environments for nurturing innovation for all students, regardless of their academic ability.